Annexin A2 regulates unfolded protein response via IRE1–XBP1 axis in macrophages during P. aeruginosa infection. Issue 2 (22nd November 2020) - Zhou, Chuan-Min; Luo, Li-Mei; Lin, Ping; Pu, Qinqin; Wang, Biao; Qin, Shugang; Wu, Qun; Yu, Xue-Jie; Wu, Min
Abstract: Pseudomonas aeruginosa is a severe Gram-negative opportunistic bacterium that causes a spectrum of organ system diseases, particularly in immunocompromised patients. This bacterium has been shown to induce unfolded protein response (UPR) during mammalian infection. Annexin A2 (AnxA2) is a multicompartmental protein relating to a number of cellular processes; however, it remains unknown whether AnxA2 coordinates a UPR pathway under bacterial infection conditions. Here, we report that the endoplasmic reticulum stress inositol-requiring enzyme 1 (IRE1)–X-box binding protein 1 (XBP1) pathway was up-regulated by AnxA2 through p38 MAPK signaling following P. aeruginosa infection in macrophages, whereas ATF4 and ATF6 not. In addition, XBP1 was found as a positive regulator of innate immunity to tame P. aeruginosa challenges by enhancing autophagy and bacterial clearance. XBP1 also facilitated NF-κB activation to elicit the release of proinflammatory cytokines predominantly in macrophages. Together, our findings identify AnxA2 as a regulator for XBP1-mediated UPR pathway. Graphical Abstract: AnxA2 plays a role in IRE1–XBP1 pathway of ER stress induced by P. aeruginosa infection through inhibition of phospho–p38 MAPK.